Analisis Luas Ruangan Berdasarkan Kebutuhan Rak di Ruang Penyimpanan Rekam Medis Rawat Jalan di RS X Kota Bandung - Arum Putri Ramdini; Ria Khoirunnisa Apriyani (Syntax Corporation Indonesia, 2021)
Organizing medical records is an activity process that begins when the patient is received at the hospital, medical records are stored in storage racks so that their confidentiality is maintained, avoids damage and makes it easier for officers to retrieve and return medical records. The purpose of this study was to analyze and determine the area of the room based on the need for shelves in the outpatient medical record file storage room at X Hospital, Bandung city The research used was descriptive quantitative, the data source was obtained from the area of the room, the average patient visits, the number of storage racks, the size of the storage rack and the thickness of the medical record file. The results showed that in the last 3 years (2018-2020) the area of the medical record storage room was 75m2, the number of patient visits was 12672 people, the number of additional storage racks was 2 units of shelves that required a room area of 11m2, the size of the storage rack was 4000cm with a distance between shelves was 100cm, and the average thickness of medical record files was 5.4cm. The results of the calculation based on the area of the room and the need for shelves in the medical record file storage room, it can be concluded that in the storage room of X Hospital, Bandung city 2 units of storage racks for medical record files need to be added without the need for additional storage spaceg